If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2x = 3 + -2x Solving 9 + 2x = 3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 2x + 2x = 3 + -2x + 2x Combine like terms: 2x + 2x = 4x 9 + 4x = 3 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 4x = 3 + 0 9 + 4x = 3 Add '-9' to each side of the equation. 9 + -9 + 4x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 3 + -9 4x = 3 + -9 Combine like terms: 3 + -9 = -6 4x = -6 Divide each side by '4'. x = -1.5 Simplifying x = -1.5
| 6r-26=-23+5r | | x-2.6x=-10 | | 4(-18-6)=6(-18+2) | | 7a(3b+4c)+g= | | -13d+7d=72 | | 2a-8=3a-8 | | 4b-1=4b-1 | | 7p+11=-9p | | 4.1x+47.5=8.8-8.8x | | 2x*50=90 | | 2x+1y=-9 | | 8(6a-4)-1=12-6a | | v^2-5v-8=0 | | -2=-(y-8) | | I=162-w | | 7+6s-1=7s+20-3s | | 180=(6x+20)+2x | | 6ab=5a-5b | | -36=-9a | | 7x+2(6x-3)=89 | | 2b-17a+cx=13y-5 | | 2x-2=-24 | | 56=-5n-2n | | 2v-6=8 | | -9+20=-19x-4-18x | | 7x+3(x-7)=89 | | 5(x-5)=20x | | -8+2s=0 | | 7x+4(6x-13)=165 | | 8=10-2h | | 3.0= | | 11x+0=8-6 |